APC/Cdh1 targets PECAM‐1 for ubiquitination and degradation in endothelial cells. Issue 3 (5th September 2019) - Liu, Jia; Yao, Qinyu; Xiao, Lei; Li, Fan; Ma, Wen; Zhang, Zihui; Xie, Xinya; Yang, Chunmiao; Cui, Qi; Tian, Ying; Zhang, Chao; Lai, Baochang; et al.
Abstract: Platelet endothelial cell adhesion molecule‐1 (PECAM‐1) is a member of the immunoglobulin superfamily and is expressed by hematopoietic and endothelial cells (ECs). Recent studies have shown that PECAM‐1 plays a crucial role in promoting the development of the EC inflammatory response in the context of disturbed flow. However, the mechanistic pathways that control PECAM‐1 protein stability remain largely unclear. Here, we identified PECAM‐1 as a novel substrate of the APC/Cdh1 E3 ubiquitin ligase. Specifically, lentivirus‐mediated Cdh1 depletion stabilized PECAM‐1 in ECs. Conversely, overexpression of Cdh1 destabilized PECAM‐1. The proteasome inhibitor MG132 blocked Cdh1‐mediated PECAM‐1 degradation. In addition, Cdh1 promoted K48‐linked polyubiquitination of PECAM‐1 in a destruction box‐dependent manner. Furthermore, we demonstrated that compared with pulsatile shear stress (PS), oscillatory shear stress decreased the expression of Cdh1 and the ubiquitination of PECAM‐1, therefore stabilizing PECAM‐1 to promote inflammation in ECs. Hence, our study revealed a novel mechanism by which fluid flow patterns regulate EC homeostasis via Cdh1‐dependent ubiquitination and subsequent degradation of PECAM‐1. Abstract : Pulsatile shear stress (PS) leads to platelet endothelial cell adhesion molecule‐1 (PECAM‐1) ubiquitination and subsequent degradation by APC/Cdh1, which, in turn, maintains endothelial cell (ECs) homeostasis. When ECs are subject to oscillatory shear stress (OS), cyclin A is upregulated, resulting in the degradation of Cdh1. As a consequence, the protein stability of PECAM‐1 is enhanced, thereby causing inflammation and contributing to atherosclerosis.